Determination and statistical treatment of short-circuit currents for faults on the lines of networks of 440 kV CESP system - Bovolato, Luiz Fernando [UNESP]; Ribeiro, Fernando Selles [UNESP]; Galvao, Luiz Claudio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1995)
The distribution of short-circuit current is investigated by means of two methods, one direct and the other analytic; both methods consider uniform probability distribution of line faults. In the direct method, the procedure consists of calculating fault currents at equidistant points along the line, starting from one of the end points and considering the other end open. The magnitude of the current is classified according to Brazilian standards (regulation NBR-7118). The analytic method assumes that the distribution of short-circuit currents through the busbar and the distribution of the line length connected to it are known, as well as the independence of values. The method is designed to determine the probability that fault currents through a line will surpass the pre-established magnitude, thus generating frequency distribution curves of short-circuit currents along the lines.
Keywords: Busbars; Calculations; Electric current distribution; Electric impedance; Electric lines; Electric power systems; Networks (circuits); Probability; Statistical methods; Brazilian standards; Feeding bus; Short circuit currents